Economic Review of the effectiveness of Natural Resource Management in improving the national economy - Setiawan, Bagus; Astina, Ria; Pramita, Cindi (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the effectiveness of Natural Resource Management (SDA) in improving the national economy with a descriptive qualitative approach. The Data was obtained through in-depth interviews, document analysis, and case studies from several countries that have implemented different natural resources management policies. The results showed that countries with sustainability-based natural resource management policies, such as the implementation of strict regulations, transparency of governance, and downstream industries, were able to increase the contribution of natural resources to national economic growth. Conversely, countries that still rely on exports of raw materials with no added value tend to face economic volatility due to fluctuations in global market prices. In addition, inequality in the distribution of Natural Resources benefits is also a major problem, where most of the benefits are only enjoyed by a few parties, while the affected local communities do not get the corresponding benefits. Therefore, the study recommends strengthening regulation, investment in the processing industry, as well as the application of circular economy principles to ensure sustainable and inclusive management of Natural Resources.